(untitled) (Raparin Journal of Humanities (RJH), 2025)
The present study seeks to investigate (The Impact of the Judd and Lavoie Model on Acquiring of Geographic Concepts Among Eighth-Grade Female Students in Social Studies). In order to meet the research aims and test its hypotheses, the researchers employed an experimental design with partial control. The study was carried out on eighth-grade female students at Zaytoun Basic School, which is associated with Shaqlawa Education - Erbil, during the second semester of the academic year (2023 – 2024). Following deliberate selection from the schools within the research population, a sample of 84 female students was randomly selected. In this regard, 42 students were assigned to the experimental group, where they were taught Geography using the Judd and Lavoie model, while the remaining 42 students formed the control group and were taught the subject using traditional methods. Subsequently, the researchers ensured equivalence between the two groups by matching them in terms of variables such as chronological age in months, intelligence, previous year’s grades in Social Studies, mothers’ qualifications, and fathers’ qualifications. Additionally, the researchers identified 18 geographical concepts and established three behavioral objectives for each concept based on the processes of concept acquisition they adopted (definition, understanding, application). The total count of these objectives was 90. Furthermore, a test containing 40 items of multiple-choice questions was developed to assess the female students’ understanding of geographical concepts. The test underwent scrutiny to ensure its validity, reliability, and the effectiveness of the incorrect answer choices. Following the conclusion of the experiment, the researchers administered the research instrument to both groups remotely. The response sheets were then gathered, assessed, analyzed, and statistically processed using the Statistical Package for the Social Sciences (SPSS) software. The obtained results were as follows: The female students in the experimental group demonstrated superior performance compared to those in the control group in the Acquiring geographical concepts test. Based on these findings, the researchers drew several conclusions, recommendations, and suggestions.